Envelhecer com dor crônica: um estudo socioeconômico, cultural e demográfico de mulheres com fibromialgia - Hayar, Maria Angélica Schlickmann Pereira (2013)
The present study aims at investigating the aging process of women affected by fibromyalgia, as well as the physical, personal and social impacts of this disease. It is a descriptive, prospective, retrospective, quantitative and qualitative research, for which the following instruments have been used: Socioeconomic, cultural and demographic profile of users of the Clinical Research Center of the DMR HC FMUSP, Fibromyalgia Impact Questionnaire (FIQ) and oral testimonies. The investigation included 66 women diagnosed with fibromyalgia, aged between 30 and 68 years old, living in Sao Paulo/SP. Quantitative research focused on analyzing data from 66 women, gathered by social workers in routine, face-to-face interviews at the Clinical Research Center of HC FMUSP. Quantitative research was treated by statistical methods, and data were demonstrated by means of graphs and tables. For qualitative research, a group of fifteen (15) out of the 66 women was selected at random: five (05) aged between 30 and 49 years, five (05) women between 50 and 59 years old, and five (05) aged 60 years and above. Individual, semi structured interviews designed by the author were conducted, recorded and later transcribed verbatim. The instrument sought to encourage subjects to reflection, in order to access social representations of pain, of the disease and of aging with chronic pain. Collective Subject Discourse technique was used as methodological procedure for processing the data of qualitative research. Data indicated greater incidence of fibromyalgia among elderly women, but the impact on quality of life, as measured by the FIQ, was higher among the middle aged group (50 to 59 years). There have been greater prevalence of the disease among women with low education, but it was found that the impact of fibromyalgia was more significant to women with higher education. The presence of religiosity was clear in this group of subjects. The physician-patient relationship was highlighted as an important factor to face adversities caused by the disease, due to the need of social legitimization of the illness. Primary care, as provided by the Family Health Strategy, requires an adequate approach to the person with such a peculiar chronic illness, as it is fibromyalgia. This approach should be extended to the elderly, in observation to the policy of humanization of SUS for health promotion